The Influence of Financial Literacy Level, Lifestyle, Fear Of Missing Out On Investment Decisions in Medan Millennial Generation Stocks - Sheerina Said Mazruk; M. Ikhsan Harahap; Andri Soemitra (Penerbit Jurnal Indonesia, 2023)
This study aims to describe and determine the effect of the level of financial literacy, lifestyle, fear of missing out on stock investment decisions in the millennial generation in the city of Medan. This research approach uses quantitative research. The data used in this study are primary data obtained from questionnaires. The sample of this research is the Millennial Generation in the city of Medan, totaling 100 respondents. The analysis technique uses the associative method which explains the causal relationship and influence between variables through hypothesis testing. The variables in this study consist of the independent variables, namely financial literacy, lifestyle and fear of missing out, and the dependent variable, namely stock investment decisions. The results of the study show that financial literacy, lifestyle and fear of missing out have a positive and significant effect on stock investment decisions simultaneously. The results of the research partially show that financial literacy has a significant effect on decisions, lifestyle has a significant effect on decisions, and fear of missing out has a significant effect on decisions.